DIAGNOSTICS AND TREATMENT OF THROM-BOSIS OF THE GREAT SAPHENOUS VEIN STUMP - Ляховський, В.І.; Demianiuk, D.G.; Bezkorovainyi, O.M.; Ляховська, Т.Ю.; Borkunov, A.L. (World of Medicine and Biology, 2012)
17 patients with thrombosis in the great saphenous vein stump were observed in a clinic during 2001-2010 years. Men were 2 (11.8%), women - 15 (88.2%). The age of patients was 48 to 62 years. With regard to varicose veins patients were operated on general surgical department from 3 months to 1.5 years ago. GSV stump thrombosis with the spread of the lumen of the femoral vein detected by means of ultrasonic color angioscanning. All patients were operated on urgently. At the same time a blood clot from the femoral vein was removed. All the patients recovered.
Keywords: thrombosis; stump; great saphenous vein